PENGARUH AKTIVITAS PERTAMBANGAN TERHADAPTATA GUNA LAHAN DAN PEREKONOMIAN MASYARAKATDI KECAMATAN PALANGGA SELATANKABUPATEN KONAWE SELATAN - Kardin Kardin; La Ode Muh. Harafah; Lukman Yunus (Universitas Halu Oleo, 2020)
ABSTRACT This study aims (1) to analyze changes in land cover/use due to mining activities in South Palangga Sub-District, South Konawe District, (2) to analyze the effect of mining activities on the community's economy in South Palangga Sub-District, South Konawe District; (3) Analyze the mining area development strategy in South Palangga Sub-District, South Konawe District. The sample was determined by random sampling with a sample of 99 respondents. Data collection methods in this study were field observations, making and filling out questionnaires. The data analysis in this study used the analysis of changes in land cover/use, analysis of difference test/cross-tabulation, and analysis of Swot.The results of this study show (1) Changes in land cover/use due to mining activities in Palangga Selatan District, South Konawe Regency since mining activities until 2019 in Palangga Selatan District reached an area of 503.33 Ha consisting of 421.96 Ha non-mining in IUP while 81.37 is not mining outside IUP. Changes in land use due to mining activities consisted of thickets covering 374.43 hectares, mixed dry land farming of 80.24 hectares, secondary dry land forests of 43.18 hectares, secondary mangroves of 5.21 hectares, and ponds of 0.27. Ha; (2) Mining activities have a positive effect on people's income and livelihoods in Palangga Selatan District, Konawe Selatan Regency. Community income that has an influence due to mining activities is 62 respondents consisting of 43 respondents with increased income and 19 respondents experiencing decreased income. Livelihood changes for 35 people with various livelihoods consisting of 31 influential respondents and 4 respondents who did not affect mining activities; and (3) the development strategy of mining areas in Palangga Selatan District, Konawe Selatan Regency is (1) Development of mining activities to increase community income and absorb new local workers; (2) Strengthening regulations related to land clearing outside IUP to prevent environmental damage; and (3) Increasing new technology to increase the absorption of new local workers. Keywords: Mining Activities, Land Use/Cover, Community Economy